Civility and mobility: Drivers (and passengers) appreciating the actions of other drivers. (March 2019) - Laurier, Eric
Abstract: My analysis centres on a dominant aspect of civility between vehicles: appreciation. I examine the inter-vehicular interaction that precedes and accompanies the 'hand-up', before then widening the analysis to consider the 'thank you' and its role in the intra-vehicular activities of driver and passenger. I differentiate between the weaker expectations of appreciation when vehicles are passing by one another and the stronger expectation involved in 'letting in' or 'letting out'. In considering how rights of way are waived by drivers, I make a contrast with a cost-benefit analysis of request and offers. The article draws upon video recordings of car journeys made by families, friends and commuters. Highlights: Interactional study of civility in traffic offering a counterpoint to the popular focus on 'road rage'. Provides details, using conversation analysis, of how 'thanking' as is produced as a second action after a first. Considers the difference between 'let past' and 'let in', where the latter action has a higher expectation of appreciation. Situates the monitoring and appreciation of other driver's offers in the driver-passenger relationship. Draws upon video recordings of ordinary car driving practices and documents them in graphic transcript format.